KARAKTERISTIK FISIK DAN LISTRIK BELIMBING WULUH UNTUK PEMBUATAN AKI ORGANIK - Moh Fikri Pomalingo; Elfransius Sinaga; Amos Axel Sinaga; Paulus Pius Pora Dosy; Bastian Rikardo Parhusip; Julfran Devit Damanik; Djami Olii; Desi Rinnawati Sinaga (Steam Engineering, 2022)
The development of science and technology has made significant advances in the search for alternative energies to replace oil and coal. One of the widely studied alternative energies is electrical energy obtained from plants. The use of electrical energy is due to the increasing population. This increase results in people using electricity to fulfill their activities and lifestyle. An alternative energy from plants is star fruit. Starfruit is acidic and contains many good electrolytes for electricity. The results of the research related to the belief in Wuluh were carried out by researchers. Based on a 2: 1 ratio (earth and star fruit) it can produce 1V of electricity. When this concept is produced in large quantities and connected in series, it can produce greater electrical power. The research was excellent and laid the foundation for the team to develop various concepts. The plan is to manufacture the battery on a large scale so that it can later be used in areas without a power supply. This battery is also said to help illuminate public roads as an alternative to replacing solar panels.